Evaluating the Effect of Addition of Titanium Dioxide Nanoparticle on Some Physical Properties of Flowable Composite Resin (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: The flowable dental composite resins were introduced to the dental specialty because of the advantages they possess over the conventional composite resins. The use of nanotechnology in the dentistry field is one of the growing innovations in recent years. The aim of the present study was to evaluate certain physical properties of flowable dental composite after incorporation of titanium dioxide nanoparticles (TiO2NPs). Materials and Method: In the present study, TiO2NPs at 1.25 % and 2.5% concentrations were added to flowable composite, while the unmodified composite was used as control. Then the physical properties of the control and modified composite resins, including flowablity, radiopacity and water sorption and solubility were tested. Data were analyzed with One way ANOVA, using SPSS 20. Results: The results showed that there was statistically significant difference among the tested groups regarding flowability and radiopacity (P<0.05). In addition, there was no significant difference among control group and TiO2 modified groups regarding water sorption and solubility. Conclusion: Based on the results of the present study, a flowable dental composite was successfully reinforced with TiO2. Incorporation of small weight percentages of this nanofiller exhibited properties similar to the control material regarding water sorption and solubility. The flowability was slightly reduced and radiopacity of the reinforced composites was increased, these changes were acceptable for clinical applications and below ISO standards limits.